Keeping Harmony Preserving Humanity: the Implementation of Tolerance and Diversity of the Society in Ngargoyoso Village, Karanganyar, Central Java - Rohmatul Faizah; Jihan Avie Yusrina (Universitas Nurul Jadid, 2022)
This study was based on the rise of issues in the name of religion in Indonesia and a response regarding the low tolerance attitude between Indonesian people towards the activities carried out by people with different religions. It is essential to reveal the best practice of harmony between the religious people as a reference in fostering a harmonious inter-religious life and dismissing the issues that have been reported louder than genuine tolerance. The best practice of this harmonious life could be found in Ngargoyoso Village, Karanganyar, Central Java, a village with multi-religious communities, such as Islam, Hinduism, and Christianity. Accordingly, this research will capture the tolerance condition in Ngargoyoso and uncover the implementation of tolerance and diversity in society. Qualitative research with a case study approach will answer these two questions. The result indicated that the harmony in Ngargoyoso has lived for a long time and has been maintained until now. The harmonious attitude was based on full awareness by the community. The spirit of cooperation also melts within society so that they have a sense of love for each other without considering religion. The implementation of tolerance and diversity was based on the appreciation of the value of Pancasila. Therefore, harmony and togetherness live. The limits of tolerance were also limited to social affairs and were not involved in matters of worship. Various efforts to maintain a well-established tolerance continue to be carried out, including assistance from outside parties and the holding of tolerance festivals.